1978
DOI: 10.2307/1128754
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of the Expectations of Parents and Teachers for the Behavior of Preschool Children

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In keeping with this description, studies comparing parents and early childhood teachers show differences in their assessments ofindividual children's behavior (Gr ay, Clancy, & King, 1981), in their disciplinary practices and interaction styles (Alston, 1982;Long & Garduque, 1987) , and in their child rearing expectations and values (Ispa, 1994;Winetsky, 1978).…”
mentioning
confidence: 89%
“…In keeping with this description, studies comparing parents and early childhood teachers show differences in their assessments ofindividual children's behavior (Gr ay, Clancy, & King, 1981), in their disciplinary practices and interaction styles (Alston, 1982;Long & Garduque, 1987) , and in their child rearing expectations and values (Ispa, 1994;Winetsky, 1978).…”
mentioning
confidence: 89%
“…Galinsky (1990) found that white mothers were viewed more positively by black caregivers. Winetsky (1978) found that a preference for child self-direction was shared by caregivers (regardless of ethnicity and SES) and Anglo middle-class parents. Non-anglo, low SES Downloaded by [Computing & Library Services, University of Huddersfield] at 15:20 26 December 2014 Kontos (1987) suggested that parents and teachers also differ in the behaviors they value in children.…”
mentioning
confidence: 96%
“…Such differences may lead to negative feelings between parents and caregivers. Winetsky (1978) found that working class parents and non-Anglo middle class parents have different educational values than teachers. Further, Kontos and dunn (1989) found that mothers whose parenting skills were held in low or high esteem by daycare staff differed in their child-rearing values.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Scientists have expressed concern regarding the continuity of behavioral expectations across the two institutions. Are values and socialization practices the same at home and school or are they different (31,35)? In addition, what is the relationship between the child's behaviors at home and at school?…”
mentioning
confidence: 99%